1981
DOI: 10.3171/jns.1981.55.2.0318
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological study of dysplastic gangliocytoma

Abstract: A case of dysplastic gangliocytoma of the cerebellum (Lhermitte-Duclos disease) is reported. Computerized tomography revealed a nonenhancing mass lesion surrounded by areas of calcification. Surgical excision resulted in complete resolution of the patient's symptoms. The histological findings support the concept that this tumor represents a congenital abnormality in granule-cell migration and is not a true neoplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 5 publications
0
28
1
Order By: Relevance
“…In patients with epilepsy, surgical treatment commonly significantly reduces or eliminates seizures. As would be expected from CT and MR, the tumor on angiography is an avascular mass (Roski et al 1981;Sabin et al 1988;Faillot et al 1990;Murata et al 1999). Gangliocytomas associated with endocrine dysfunction may require medical management of the endocrinopathy (McCowen et al 1999;Isidro et al 2005).…”
Section: Treatment and Clinical Outcomementioning
confidence: 79%
“…In patients with epilepsy, surgical treatment commonly significantly reduces or eliminates seizures. As would be expected from CT and MR, the tumor on angiography is an avascular mass (Roski et al 1981;Sabin et al 1988;Faillot et al 1990;Murata et al 1999). Gangliocytomas associated with endocrine dysfunction may require medical management of the endocrinopathy (McCowen et al 1999;Isidro et al 2005).…”
Section: Treatment and Clinical Outcomementioning
confidence: 79%
“…However, complete resection may be difficult because of poorly defined margins, leading to a high risk of recurrence. For this reason and given the slowly-growing nature of LDD, a long-term follow-up is required 30 31. However, our case highlights that prompt and aggressive surgical treatment can prevent significant visual loss, normalise the peripapillary retinal nerve fibre layer and preserve the visual field.…”
Section: Discussionmentioning
confidence: 90%
“…[7][8][9] In a few instances, patients with Lhermitte-Duclos disease have undergone radiation therapy, but the effect of posterior fossa irradiation has been variously reported to either result in several symptomfree years 31 or progressive neurological deterioration. 14 Decompressive surgery for symptomatic patients has been successful both in relieving symptoms 9,12,25,32 and in improving long-term survival from 2.5 to 11 years. 12,13,30,32 The lesion usually blends into normal cerebellar parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The recognition of the coexistence of Lhermitte-Duclos disease and multiple hamartoma-neoplasia syndrome, also called Cowden syndrome, by Padberg et al 17 suggested a genetic association between the two entities. 1 Today Lhermitte-Duclos disease or dysplastic gangliocytoma of the cerebellum is still a highly unusual and controversial condition.…”
Section: Introductionmentioning
confidence: 99%